Polyanhydride nanovaccine against swine influenza virus in pigs. Issue 8 (22nd February 2017) - Dhakal, Santosh; Goodman, Jonathan; Bondra, Kathryn; Lakshmanappa, Yashavanth S.; Hiremath, Jagadish; Shyu, Duan-Liang; Ouyang, Kang; Kang, Kyung-il; Krakowka, Steven; Wannemuehler, Michael J.; Won Lee, Chang; Narasimhan, Balaji; et al.
Abstract: We have recently demonstrated the effectiveness of an influenza A virus (IAV) subunit vaccine based on biodegradable polyanhydride nanoparticles delivery in mice. In the present study, we evaluated the efficacy of ∼200 nm polyanhydride nanoparticles encapsulating inactivated swine influenza A virus (SwIAV) as a vaccine to induce protective immunity against a heterologous IAV challenge in pigs. Nursery pigs were vaccinated intranasally twice with inactivated SwIAV H1N2 (KAg) or polyanhydride nanoparticle-encapsulated KAg (KAg nanovaccine), and efficacy was evaluated against a heterologous zoonotic virulent SwIAV H1N1 challenge. Pigs were monitored for fever daily. Local and systemic antibody responses, antigen-specific proliferation of peripheral blood mononuclear cells, gross and microscopic lung lesions, and virus load in the respiratory tract were compared among the groups of animals. Our pre-challenge results indicated that KAg nanovaccine induced virus-specific lymphocyte proliferation and increased the frequency of CD4 + CD8αα + T helper and CD8 + cytotoxic T cells in peripheral blood mononuclear cells. KAg nanovaccine-immunized pigs were protected from fever following SwIAV challenge. In addition, pigs immunized with the KAg nanovaccine presented with lower viral antigens in lung sections and had 6 to 8-fold reduction in nasal shedding of SwIAV four days post-challenge compared to control animals. Immunologically, increased IFN-γ secreting T lymphocyte populations against both the vaccine and challenge viruses were detected in KAg nanovaccine-immunized pigs compared to the animals immunized with KAg alone. However, in the KAg nanovaccine-immunized pigs, hemagglutination inhibition, IgG and IgA antibody responses, and virus neutralization titers were comparable to that in the animals immunized with KAg alone. Overall, our data indicated that intranasal delivery of polyanhydride-based SwIAV nanovaccine augmented antigen-specific cellular immune response in pigs, with promise to induce cross-protective immunity.